2010
DOI: 10.1080/10406631003608479
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study on Benzotrifuroxan and its Isomers

Abstract: Benzotrifuroxan is a powerful, hydrogen-free explosive material. It also has an interesting chemistry. Through ring opening and reclosure mechanisms, various isomers are likely to form. In the present study, within the density functional theory (B3LYP/6-31G(d)), isomeric benzotrifuroxans, dinitrosobenzodifuroxans, and tetranitrosobenzomonofuroxans as well as hexanitrosobenzene have been investigated. Also, the monoionic forms of some of these have been considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Computational studies are helpful to investigate the interesting and challenging chemistry exhibited by benzofuroxan and its derivatives (29)(30)(31)(32)(33)(34). One of the striking behavior of BFO is the molecular rearrangement of it which involves 1,2-dinitroso benzene intermediate (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies are helpful to investigate the interesting and challenging chemistry exhibited by benzofuroxan and its derivatives (29)(30)(31)(32)(33)(34). One of the striking behavior of BFO is the molecular rearrangement of it which involves 1,2-dinitroso benzene intermediate (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…BTF was first synthesized by Turek in 1931 [3], and its synthetic route has been improved in recent years to satisfy its wide application in energetic fields [4]. BTF has attracted much attention in many areas due to its unique advantages including high energy, zero oxygen balance, and low shock sensitivity [5]. The density of BTF (1.90 g cm À 3 ) is higher than that of RDX (1.79 g cm À 3 ), and BTF shows higher detonation velocity (8277 m s À 1 ) compared to TATB (7606 m s À 1 ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Makhova and Fershtat, outlined recent advances in the synthesis and functionalization of 1,2,5-oxadiazole-2-oxides [2]. Some computational studies on structures having furoxan systems have been reported recently [3][4][5][6]. Some energetic compounds possessing 1,2,5-oxadiazole 2-oxide system have been reported [7].…”
Section: Introductionmentioning
confidence: 99%